PENERAPAN SISTEM FIRST IN FIRST OUT TERHADAP BAHAN PANGAN BASADI DAPUR BEST WESTERN PREMIERE PANBIL HOTEL BATAM - Agustiar; Yulia Mandasari (Jurnal Pariwisata Bunda, 2020)
This study aims to describe the application of the first in first out system to wet food in terms of the wet material storage system. This research is descriptive qualitative. The object of this research is the first in first out system for wet food ingredients. The data sources are employees of the Best Western Premier Panbil hotel kitchen. Data collection techniques are observation, interviews and documentation. Data analysis techniques are data reduction, display data, drawing conclusions and verification. The results of this study illustrate that wet food storage is not applied at full events. This can be seen when the event is full, especially at the Banquet event where the production at the Best Western Premiere Panbil Batam kitchen reaches thousands of pax. This event is almost every day full so that the items in storage are often messy and when new items enter the kitchen staff often immediately enter and stack them in the basket without scanning where the new stock items are the old ones. They often do this because they are pursuing a target time to produce or focus more on handling the Banquet event at the Best western Premiere Panbil Batam hotel. In the storage of foodstuffs, it should be grouped and adjusted according to its type, starting from the level of hardness of the foodstuff and the mass of the foodstuff.